2018
DOI: 10.1029/2018gl078507
|View full text |Cite
|
Sign up to set email alerts
|

Pore‐Scale Visualization of Methane Hydrate‐Bearing Sediments With Micro‐CT

Abstract: X‐ray computed tomography (CT) has become a critical technique in the study of porous media. It has attracted growing attention for analyzing hydrate‐bearing sediment, but this has been done using surrogates (Xe/Kr) only due to difficulties in distinguishing methane hydrate from water. This study presents the successful imaging of methane hydrate coexisting with pore liquid, gas, and sediments. We used potassium iodide (KI) solutions and in‐line propagation‐based phase‐contrast CT analysis of X‐ray attenuation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
69
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(71 citation statements)
references
References 35 publications
1
69
1
Order By: Relevance
“…This leads to the grayscale level of methane hydrate in Figure c lying in the middle position between grayscale levels of methane gas and NaCl solution. This kind of grayscale level distribution for methane gas, methane hydrate, and solution is quite consistent with those reported by Lei et al () and Li et al ().…”
Section: Theory and Experimental Methodssupporting
confidence: 92%
See 1 more Smart Citation
“…This leads to the grayscale level of methane hydrate in Figure c lying in the middle position between grayscale levels of methane gas and NaCl solution. This kind of grayscale level distribution for methane gas, methane hydrate, and solution is quite consistent with those reported by Lei et al () and Li et al ().…”
Section: Theory and Experimental Methodssupporting
confidence: 92%
“…The bulk porosity of A‐graded and B‐graded host sands is controlled between 37% and 38%, and the initial water saturation is about 0.5. For reference, various kinds of solutions used as alternatives to pure water can keep enhancing the phase contrast between hydrate and solution in X‐ray CT images during hydrate formation due to the increasing solute concentration (Chen et al, ; Kerkar et al, ; Lei et al, ; Li et al, ; Ta et al, ).…”
Section: Theory and Experimental Methodsmentioning
confidence: 99%
“…They concluded that all the resultant images showed a water film between hydrate and sand. However, Lei et al () got an opposite conclusion by using phase‐contrast CT in their study. They developed a new imaging method for distinguishing methane hydrate from water and found that a low density thin layer on the surface of sand particles is more likely to be caused by diffraction rather than a real water layer.…”
Section: Introductionmentioning
confidence: 83%
“…They developed a new imaging method for distinguishing methane hydrate from water and found that a low density thin layer on the surface of sand particles is more likely to be caused by diffraction rather than a real water layer. Whether there is a water layer between hydrate and sand particles is still controversial (Lei et al, ; Sell et al, ). In view of the water film, gray value curves of CT image were helpful to identify the boundaries between hydrates and quartz sands (Hu et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Phillips et al (2019) and Santamarina et al (2015) suggest that local freshening at the pore scale has a first-order control on dissociation. Recent micro-CT work by Lei et al (2018) has directly observed hydrate formation in pores and associated changes in salinity. Microfluidics (e.g., Kang et al, 2016;Martinez de Baños et al, 2015) and micro-Raman (e.g., Davies et al, 2010;Prasad et al, 2009) experiments have visually investigated and analyzed the dynamic processes of hydrate formation and dissociation.…”
Section: Future Studies To Illuminate How Hydrate Systems Formmentioning
confidence: 99%